Melanocortin receptor accessory proteins in adrenal disease and obesity - Jackson, David S.; Ramachandrappa, Shwetha; Clark, Adrian J.; Chan, Li F. (Frontiers in Neuroscience, 2015)
Melanocortin receptor accessory proteins (MRAPs) are regulators of the melanocortin receptor family. MRAP is an essential accessory factor for the functional expression of the MC2R/ACTH receptor. The importance of MRAP in adrenal gland physiology is demonstrated by the clinical condition familial glucocorticoid deficiency type 2. The role of its paralog melanocortin-2-receptor accessory protein 2 (MRAP2), which is predominantly expressed in the hypothalamus including the paraventricular nucleus, has recently been linked to mammalian obesity. Whole body deletion and targeted brain specific deletion of the Mrap2 gene result in severe obesity in mice. Interestingly, Mrap2 complete knockout (KO) mice have increased body weight without detectable changes to food intake or energy expenditure. Rare heterozygous variants of MRAP2 have been found in humans with severe, early-onset obesity. In vitro data have shown that Mrap2 interaction with the melanocortin-4-receptor (Mc4r) affects receptor signaling. However, the mechanism by which Mrap2 regulates body weight in vivo is not fully understood and differences between the phenotypes of Mrap2 and Mc4r KO mice may point towards Mc4r independent mechanisms.